Continuing healthcare education: a strategy to connect teaching and services - Luiz Alves Morais Filho; Cristiane da Silva Ramos Marinho; Vânia Marli Schubert Backes; Jussara Gue Martini (Universidade Federal do Ceará, 2013)
This experience report aims to describe the experience of implementing a project for continuing education with the nursing staff of the emergency service at three hospitals, highlighting the connection between teaching and service. This project was developed by professors and undergraduate nursing students of the Universidade Federal do Rio Grande do Norte in 2011, and conducted at the urgent care services of three hospitals. In each hospital were worked themes chosen by service professionals according to local needs. At the meetings, we used questioning with daily issues, round-table discussions of professional experiences, practical classes in the emergency care facility and laboratory, discussion of texts, and lecture/dialogue classes. The experience of this project reveals the importance and potential of integrating teaching-services in the continuing education of health workers in order to improve care quality and solidify the National Health System in Brazil